2020
DOI: 10.3356/0892-1016-54.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nest Box Installation on a Distribution Power Line: Increased Eurasian Kestrel Nesting, Reduced Electrocutions, and Reduced Electrical Faults

Abstract: Electrical pylons are frequently used by birds for perching, roosting, and nesting. These behaviors can lead to electrocutions, particularly when pylons are constructed of grounded concrete and steel crossarms, as they were in our study area near Arak, Iran. To address electrocutions of Eurasian Kestrels (Falco tinnunculus) and a variety of passerines nesting on a 20-kV distribution line, we documented construction and use of nests on pylons on a 34-km segment of power line in 2018. Following removal of nests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…The occurrence of birds nesting on electric infrastructure is well‐known globally (Ferrer 2012, Dwyer and Dalla Rosa 2015, Moreira et al 2018, Kolnegari et al 2020 a ) but the extent of nesting is not as well understood, partly because ornithologists are unable to visit all of the considerable electrical infrastructure that exists worldwide. We used crowd‐sourced data from electric utility linemen to broaden our knowledge of birds nesting on power lines in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The occurrence of birds nesting on electric infrastructure is well‐known globally (Ferrer 2012, Dwyer and Dalla Rosa 2015, Moreira et al 2018, Kolnegari et al 2020 a ) but the extent of nesting is not as well understood, partly because ornithologists are unable to visit all of the considerable electrical infrastructure that exists worldwide. We used crowd‐sourced data from electric utility linemen to broaden our knowledge of birds nesting on power lines in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of intervention, Eurasian magpies will presumably continue to nest on 63‐kV structures. These nests generally will not create safety or reliability concerns for electric utilities, but if Eurasian magpies create conservation concerns for other species, as corvids sometimes do elsewhere (Jerzak 2001, Marzluff and Neatherlin 2006), then approaches such as installing nest boxes to leverage interspecific competition may be directed to 63‐kV structures (Kolnegari et al 2020 a ). We also found that 20‐kV structures supported proportionally large numbers of Eurasian magpies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations